Trabecular titanium can induce in vitro osteogenic differentiation of human adipose derived stem cells without osteogenic factors. Issue 7 (30th July 2013) - Benazzo, Francesco; Botta, Laura; Scaffino, Manuela Federica; Caliogna, Laura; Marullo, Matteo; Fusi, Simonetta; Gastaldi, Giulia
Abstract Trabecular Titanium (TT) is an innovative highly porous structure that imitates the morphology of trabecular bone with good mechanical properties. Adipose‐derived stem cells are a multipotent cell population that can be used in regenerative medicine, in particular, for bone therapeutic applications. The ability of TT to induce the osteogenic differentiation of human adipose derived stem cells (hASCs) in the absence of osteogenic factors was evaluated using molecular biological, biochemical, and immunohistochemical methods. At 7 and 21 days from differentiation, the hASCs grown on TT scaffolds showed similar expressions of alkaline phosphatase (ALP) and Runx‐2 both in the presence and in the absence of osteogenic factors, as well as at transcript and protein levels. hASCs cultured on monolayer in the presence of the medium obtained from the wells where hASCs/scaffold constructs were cultured in the absence of osteogenic factors differentiated towards the osteogenic phenotype: their gene and protein expression of ALP and Runx‐2 was similar to that of the same cells cultured in the presence of osteogenic factors, and significantly higher than that of the ones cultured in growth medium. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2061–2071, 2014.